THE ACTIVE LEARNING STRATEGY “EVERYONE IS A TEACHER HERE” TO IMPROVE STUDENT LEARNING OUTCOMES - Oriza Candra; Yanto, Doni Tri Putra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aims to determine the improvement of student learning outcomes in Analyzing Circuits (MRL) subjects in class X TDTL SMK N 1 Padang by using the active learning strategies type of Everyone is a Teacher Here. This type of research was quasi-experimental. The subjects of the research was class X TDTL with 32 students. The object of the research was active learning strategies type of Everyone Is a Teacher Here. The instrument used was the achievement test by using multiple-choice questions that had been tested for validity and reliability. From the results of the research, data showed the average value of student learning outcomes in the average pretest was 57. While at posttest by applying Active Learning Strategies Everyone is a Teacher Here, it showed an increase of 17.5 points, with an average of 74.5. The learning outcomes were tested by using Gainscore’s formula (g) which obtained 0.337 g with middle score criteria.